LEMBAGA KEUANGAN MIKRO SYARIAH: EKSISTENSI DAN AKSESIBILITASNYA BAGI PEMBIAYAAN USAHATANI DI SUMATERA BARAT (Studi Kasus: Koperasi Jasa Keuangan Syariah (KJKS) Baitul Maal Wat Tamwil (BMT)) - Widya Fitriana (Jurnal Agribisnis Indonesia, 2016)
Farm financing is one of the factors facilitating the development of agriculture which allow farmers to expand the scale of farming and adopt new technologies. Unfortunately, a number of financial institutions often perceive farmers as "unbankable poor" that is costly to finance. KJKS BMT is one financial institution that is initiated by the government of West Sumatra's mission of poverty reduction in rural areas in particular to improve the access of small farmers to credit. So this study aims to identify and analyze the existence and accessibility of financing KJKS BMT in serving the financing of farming in West Sumatra. This study was conducted in a multi-stage random sampling, cities that randomly selected are Kota Padang and Bukittinggi, and then for each city, one KJKS BMT is also randomly selected. Primary data were collected by interviewing 60 respondent’s farmers. This research uses grounded research methods and data analysis in qualitative descriptive. Period of observation data for 2 years ie 2012-2014. Existence of KJKS BMT to finance farming measured by used five indicator namely a) The number of customers, b) The number of farmer customers, c) credit share for the agricultural, d) The number of farm financing and e) Development of BMT’s human resources. Furthermore accessibility is measured using six indicators, namely: (a) access to information, (b) access to loan procedure, (c) access to the maximum limit, (d) access to the time of disbursement, (e) access to loan repayment, and ( f) facilitation of access to financing. The results show that (1) although the existence of KJKS BMT start respected by rural communities, and even show a positive growth, but the credit share given by KJKS BMT to farm credit is still very small compared to another sectors (like trade and manufactures) which are less than 5%, Even though the level of customer growth of farmers during the past two years is reach 75%, higher than the growth of total customer (2) Accessibility of KJKS BMT to farm financing overall is good, although there are several factor that must be addressed like the availability of information, the number of loan, monitoring and loan supervision.